The Influence of Financial Technology Literacy and Behavioral Bias on Generation Z Investment Decisions the Moderating Role of Fear of Missing Out (FoMO) in the Digital Economy Era - Zulkifli Djamin; Dasmadi Dasmadi; Yuliza Yuliza (Fundamental and Applied Management Journal, 2026)
This study aims to examine the influence of financial technology literacy and behavioral bias on investment decisions among Generation Z, as well as to analyze the moderating role of Fear of Missing Out (FoMO) in the digital economy era. The rapid development of digital financial platforms has increased accessibility to investment opportunities, particularly for younger generations. However, this ease of access is often accompanied by psychological factors that may lead to irrational decision-making. This research adopts a quantitative approach using a survey method, with data collected from Generation Z respondents who actively use financial technology for investment purposes. The data are analyzed using structural equation modeling (SEM) to identify the relationships between variables and the moderating effect of FoMO. The findings indicate that financial technology literacy has a significant positive effect on investment decisions, as individuals with higher literacy levels tend to make more informed and rational choices. Conversely, behavioral biases such as overconfidence, herd behavior, and loss aversion significantly influence investment decisions in a less rational direction. Furthermore, FoMO is found to strengthen the relationship between behavioral bias and investment decisions, suggesting that individuals with higher FoMO are more likely to be influenced by market trends and social pressures. The study highlights the importance of improving financial literacy and managing psychological factors to promote more rational investment behavior among Generation Z in the digital economy.